2023
DOI: 10.1038/s41467-023-36710-x
|View full text |Cite
|
Sign up to set email alerts
|

Tuning excited state electronic structure and charge transport in covalent organic frameworks for enhanced photocatalytic performance

Abstract: Covalent organic frameworks (COFs) represent an emerging class of organic photocatalysts. However, their complicated structures lead to indeterminacy about photocatalytic active sites and reaction mechanisms. Herein, we use reticular chemistry to construct a family of isoreticular crystalline hydrazide-based COF photocatalysts, with the optoelectronic properties and local pore characteristics of the COFs modulated using different linkers. The excited state electronic distribution and transport pathways in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
78
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 192 publications
(115 citation statements)
references
References 71 publications
1
78
0
Order By: Relevance
“…It is generally accepted that copper ions cause a sequence of events that eventually lead to cell death. 55–58 The antibacterial mechanism of the CHM and CMM here could also be attributed to the release of Cu 2+ ions, which initially adsorb on the cell membrane of bacteria and then infiltrate into the cells through interactions with the hydroxyl groups of peptidoglycans, causing damage to the cell membranes and DNA breakage. The SEM images were further used to observe visually the morphological changes of E. coli and S. aureus after antibacterial experiments for CMM-70 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It is generally accepted that copper ions cause a sequence of events that eventually lead to cell death. 55–58 The antibacterial mechanism of the CHM and CMM here could also be attributed to the release of Cu 2+ ions, which initially adsorb on the cell membrane of bacteria and then infiltrate into the cells through interactions with the hydroxyl groups of peptidoglycans, causing damage to the cell membranes and DNA breakage. The SEM images were further used to observe visually the morphological changes of E. coli and S. aureus after antibacterial experiments for CMM-70 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…We believe that once the formation of PAN can be widely avoided, using other monomers for copolymerization is also feasible. From the perspective of experiments and theoretical calculation, recent reports suggested that the adsorption strength of amidoxime for uranium is almost the highest. , Furthermore, the adsorption capacity of A-1 for uranium was 9.1 times higher than that of vanadium, while that of A-3 was 14.8 times. This may be due to the long distance between amidoxime groups on A-1 and the less modification amount of amidoxime.…”
Section: Resultsmentioning
confidence: 99%
“…It shows that N-TPCOP can reduce Au 3+ to gold monocrystals. 49 The presence of Au4F peaks in the full XPS spectrum is an indication that gold has been captured on N-TPCOP (Fig. 9a).…”
Section: Adsorption Mechanismmentioning
confidence: 98%